Collaborative Governance dalam Pengembangan Kawasan Wisata Goa Kelelawar Padayo Kecamatan Lubuk Kilangan Kota Padang - Meliza Aulia Putri; Artha Dini Akmal (YASIN, 2026)
The development of the Goa Kelelawar Padayo tourism area involves the Padang City Government, the community, Kelompok Sadar Wisata (Pokdarwis), and PT Semen Padang because of the limited resources of the government and community and the demands of sustainable tourism development. However, collaboration during the development stage has not fully ensured the sustainability of tourism area management. This study aimed to analyze collaborative governance in the development of the Goa Kelelawar Padayo tourism area and identify its supporting and inhibiting factors. The study employed a qualitative descriptive method with a case study approach. Data were collected through interviews, observations, and documentation and then analyzed interactively through data reduction, data presentation, and conclusion drawing. The analysis referred to Ansell and Gash’s collaborative governance framework, which encompasses starting conditions, institutional design, facilitative leadership, and the collaborative process. The results showed that collaboration was relatively strong during the initiation, planning, and development stages, as indicated by community participation, government support, PT Semen Padang’s corporate social responsibility (CSR) contributions, dialogue among actors, trust building, and the construction of tourism facilities. Nevertheless, the sustainability of the collaboration remained suboptimal because of declining coordination after the development stage, community participation that remained representative in nature, the absence of a permanent collaborative forum, dependence on CSR resources, and changes in development priorities. Factors supporting the collaboration included social capital, shared objectives, government support, and CSR, whereas the inhibiting factors comprised limited resources, weak coordination, and institutional capacity that had not yet become sustainable. These findings emphasize that the sustainable development of Goa Kelelawar Padayo requires stronger coordination among actors, broader community participation, and the establishment of a permanent collaborative institution to maintain the continuity of tourism area management.